Jaringan Sosial-Komunikasi Petani Pada Distribusi Produk Hasil Bumi Desa Jatisura Indramayu - Radita Gora Tayibnapis; Munadhil Abdul Muqsith; Ana Kuswanti; Tri Dian Hapsari; Hermina Manihuruk (Faculty of Sharia and Law UIN Syarif Hidayatullah Jakarta, 2023)
Jatisura Village has very strong agricultural and plantation potential and has adequate Natural Resources to be planted with various crops and produce promising agribusiness prospects. However, this indicates the constraints of an inadequate communication network between farmers and sellers of crops because the hierarchical network of rice, fruit and vegetable trade is too complex. Through the analysis of the communication network here with a qualitative approach, it was found that the connection between farmers and other farmers and also the relationship with middlemen, of course, farmers must be members of the Association of Farmer Groups (GAPOKTAN) and also between farmer group agents have a communication network that is so dense and provides positive measurements so that communication attachments between farmer group agents are always established and mutual communication occurs. The existence of middlemen becomes dependent on farmers so that this expands the distribution of the trade network of crops from Jatisura Village.Keywords: Communication Network, Jatisura Village, Agriculture Abstract Desa jatisura memiliki potensi pertanian dan perkebunan yang sangat kuat serta memiliki Sumber Daya Alam yang memadai untuk bisa ditanami berbagai macam tanaman serta menghasilkan prospek agrobisnis yang menjanjikan. Namun hal tersebut terindikasi kendala adanya jaringan komunikasi yang kurang memadai antara petani dan penjual hasil Bumi lantaran jaringan hierarki perdagangan beras, buah dan sayuran terlalu kompleks. Melalui analisis jaringan komunikasi disini dengan pendekatan kualitatif ditemukan bahwa keterhubungan petani dengan petani lain dan juga hubungan dengan tengkulak tentu para petani harus tergabung dengan Gabungan Kelompok Tani (GAPOKTAN) dan juga antar agen kelompok tani memiliki jaringan komunikasi yang begitu padat dan memberikan pengukuran yang positif sehingga keterikatan komunikasi antara agen kelomok tani selalu terjalin dan terjadinya komunikasi timbalik balik. Keberadaan para tengkulak menjadi ketergantungan bagi para petani sehingga hal ini yang memperluas distribusi jaringan perdagangan hasil bumi dari Desa Jatisura.Keywords: Jaringan Komunikasi, Desa Jatisura, Pertanian